Strategi Diskursif dalam Reportase Gaya Kampanye Capres Indonesia No. 2 oleh Tirto.Id - Andriani, Cindy (Crises on Languages and Literature, 2024)
Election moments always present a war of discourse as a weapon in political contestation to shape opinions. The narrative contained in a discourse is constructed by discursive strategies that can influence public perception of the election. Therefore, this study aims to (1) explain the discursive strategies used by tirto.id in conveying the campaign style reportage of Presidential Candidate Number 2 and (2) explain the historical context behind the discursive strategies used by tirto.id. This study is a qualitative descriptive study with a historical discourse analysis approach. Data collection was carried out using the listening and recording method. The data source is Instagram tirto.id about the campaign style reportage of Presidential Candidate Number 2 with the title "Citra Prabowo Dulu & Kini". The data analysis was carried out by answering a framework of questions related to five discursive strategies (Wodak, 2001:72-73). The results of the study show that the discursive strategies used are referential strategies through categorization, predication through evaluative attribution with adjectives, argumentation reinforced with topoi, perspective formation through narrative, and intensification with phrases. Meanwhile, there are 4 historical contexts found, namely the kidnapping of 98 activists and human rights violations, the 2014 and 2019 presidential elections, Prabowo's appointment as Minister of Defense in 2019, and the 2022 Philippine presidential election.